Chemical Components of Ocimum basilicum L. and Ocimum tenuiflorum L. Stem Essential Oils and Evaluation of Their Antioxidant Activities Using DPPH Method - Hikmawanti, Ni Putu Ermi; Hariyanti,; Nurkamalia,; Nurhidayah, Sahera (UI Scholars Hub, 2019)
Ocimum basilicum L. and Ocimum tenuiflorum L. are two types of plants from Ocimum (Lamiaceae). One of their chemical compounds is essential oil. Essential oil might have an antioxidant activities. The part of the plants which are often wasted and never used are stem. This study aimed to analyze the chemical components of O. basilicum L. and O. tenuiflorum L. stem essential oils and evaluate their antioxidant activities. Essential oils were obtained by steam-water distillation. Analysis of chemical component of essential oil was performed using Gas Chromatography-Mass Spectroscopy (GC-MS). Antioxidant activities were evaluated with DPPH method and then the IC50 value was determined as 50% inhibition concentration of free radical. The results showed that O. basilicum L. stem essential oil had 13 components with the major compounds were methyl eugenol (52.60%), caryophyllene (18.75%), and germacrene-D (9.19%). Whereas, O. tenuiflorum L. stem essential oil had 11 components with the major compounds were α-copaene (5.56%), caryophyllene (17.28%), germacrene-D (9.29%) and methyl eugenol (56.72%). IC50 value of O. basilicum L. stem essential oil was 17.50 µg/mL, whereas IC50 value of O. tenuiflorum L. stem essential oil was 14.17 µg/mL. It was concluded that both oils might be good natural antioxidant agents.